Structural and Mineralogical Characterization of a Fossil Hydrothermal System Located at the Outermost Front of the Southern Apennines Fold-and-Thrust Belt. (28th April 2019) - Fulignati, Paolo; Agosta, Fabrizio; Belviso, Claudia; Prosser, Giacomo; Lettino, Antonio; Petrullo, Angela Vita; Cavalcante, Francesco
Abstract : Aiming at investigating the hydrothermal circulation along the eastern flank of the Vulture volcano, along the outermost edge of the southern Apennine fold-and-thrust belt (ftb), we studied the fossil hydrothermal alteration that mineralized a transtensional fault that crosscuts volcanoclastic rocks in the Rapolla area. On the basis of structural, mineralogical, and fluid inclusion data, three main stages of activity of the hydrothermal system are documented. Stage 1 was produced by the circulation of fluids having low-pH conditions (pH ≈ 3-4) and relatively high-SO4 2- activity, as testified by the hydrothermal alteration mainly carried out by the alunite group minerals (particularly jarosite), which is typical of an advanced argillic alteration facies. Hydrothermal fluids were characterized by a high temperature of about 200°-210°C. These hot fluids altered and mineralized the matrices of pyroclastic rocks and sealed both burial-related and fault-related fracture networks. Later hydrothermal circulation (Stage 2) was recorded by opal A-rich veins present both within and outside the fault zone. The fluids responsible of opal A precipitation were characterized by lower temperature conditions, probably lower than 100°C. Current goethite mineralization takes place along the main slip surfaces of the study high-angle fault zone due to low temperature (<30°C) underground water circulation. This study highlights that a high-temperature hydrothermal system developed in the past within the transtensional fault zone of the Rapolla area when a high thermal anomaly was present. If we take into account that this area is still affected by a heat flux positive anomaly (90 mW/m 2 ), we may infer that it has the potentiality to be considered an interesting site for future exploration devoted to the finding of medium-enthalpy geothermal resources at depth.